Biocontrole in vitro de fungos toxigênicos utilizando leveduras isoladas do café e cacau - Souza, Mariana Lino de (2014)
Agricultural products such as coffee fruit and beans, grapes among others which are important for Brazilian economy may be contaminated by filamentous fungi producing ochratoxin A (OTA) from the field to storage. This mycotoxin is considered to be one of the most harmful to human health due to its toxicity. The excessive application of fungicides and the hazards to human health has led to researches into alternatives forms such as biological control. In this context, we aimed to evaluate the antagonistic potential of 32 yeast strains belonging to the genera Debaryomyces, Pichia and Saccharomyces isolated from coffee and cocoa fruit, co-cultivated with Aspergillus ochraceus and A. carbonarius. Yeasts were inoculated (104 and 107 cell/mL) with three isolates of filamentous fungi, A. carbonarius (isolated 2 and 8CSP3-25) from grape and A. ochraceus (SCM 1.9) from coffee (105 spores/mL). The mycelial growth evaluation and spores scoring both in MEA medium, and OTA production in CYA and YES media at 0.98, 0.96 and 0.94 aw was performed by Layer Chromatography (LTC) and all factors evaluated after 7 days of incubation at 28ºC. Yeasts in both concentrations (104 and 107 cell/mL) have shown higher inhibitory effect to mycelial growth (53% in comparison to control) for A. ochraceus isolate. As for spore production, Aspergillus carbonarius 2 had 38% higher spore production in comparison with A. carbonarius 8CSP 3-25. Yeasts belonging to the genus Pichia have screened a higher inhibitory effect on sporulation. Regarding inhibition of OTA production, Debaryomyces hansenii UFLA CF693, were in agreement with the three isolates of Aspergillus and the highest inhibition of OTA production took place at the 0.94 aw media. Therefore, it was possible to conclude that yeasts co-cultivated with filamentous fungi are able to inhibit mycelial growth, sporulation and OTA production. Thus, they are able to decrease the spread of these fungi during any agricultural products processing and thereafter food contamination with mycotoxin such as Ochratoxin A.